2016
DOI: 10.1080/21645515.2016.1242539
|View full text |Cite
|
Sign up to set email alerts
|

Impact of universal mass vaccination with monovalent inactivated hepatitis A vaccines – A systematic review

Abstract: The WHO recommends integration of universal mass vaccination (UMV) against hepatitis A virus (HAV) in national immunization schedules for children aged ≥1 year, if justified on the basis of acute HAV incidence, declining endemicity from high to intermediate and cost-effectiveness. This recommendation has been implemented in several countries. Our aim was to assess the impact of UMV using monovalent inactivated hepatitis A vaccines on incidence and persistence of anti-HAV (IgG) antibodies in pediatric populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 68 publications
1
48
0
1
Order By: Relevance
“…29 However, the model projections do demonstrate that reliable access to clean water in both rural and urban areas is a significant predictor of the HAV epidemiological transition.…”
Section: Discussionmentioning
confidence: 99%
“…29 However, the model projections do demonstrate that reliable access to clean water in both rural and urban areas is a significant predictor of the HAV epidemiological transition.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey has analysed the impact of such UMV programs on the incidence of hepatitis A, reported in studies conducted in Argentina, China, Greece, Israel, Panama, the US and Uruguay. 168 All except one study 169 reported a significant drop in the incidence of acute hepatitis A following introduction of UMV. Declines were documented irrespective of age at first vaccine dose (12-24 months), vaccine brand or vaccine coverage (range 25-96.8%).…”
Section: Active Immunisation With Hepatitis a Vaccinesmentioning
confidence: 99%
“…Other indirect effects of UMV included a drop in hospitalisation rates for hepatitis A in Greece; a decline in the reports on acute hepatitis A in day-care centres in Israel, 171 as well as a reduction in HAV-associated fulminant hepatitis and ageadjusted mortality and liver transplantation in Argentina. 139,168 Finally, it seems that the cyclic epidemic peaks of acute hepatitis A are also dwindling. All in all, the overall decline in the incidence of HAV infection is most probably even higher than reported, considering the low reporting rates of hepatitis A and the estimated large proportion of asymptomatic patients.…”
Section: Active Immunisation With Hepatitis a Vaccinesmentioning
confidence: 99%
“…The incidence rate varies between 6.0 and 30.0 cases per 100,000 months of stay in virtually all developing countries [71]. In children a majority of infections are asymptomatic; however, in adults the infection often leads to acute hepatitis that may result in prolonged incapacitation or to acute liver failure [72]. In the study performed by Mutsch et al [71], 5.3% of all hepatitis A cases occurred in the group of patients older than 60 years.…”
Section: Travel-related Vaccinesmentioning
confidence: 99%